Computation of some properties of Ti-Si-C and Ti-Al-N MAX phase materials - Bangani, Vuyokazi Lusanda (My University, 2010)
The "MAX" phases are a class of ductile nanolaminated ternary nitrides and car- bides, including about 60 known phases. The chemical formula for the MAX phase is Mn+1AXn where M is an early transition metal. They consists of the 211, 321 and 412 groups. There are over 40 M2AX phases in existence.The M2AC MAX phase category is divided into two subgroups, the V(B) and VI(B) transition metals. There are three M3AX2 (Ti3SiC2, Ti3GeC2 and Ti3AlC2) and one M4AX3 (Ti4AlN3): As for the 321 MAX- phases the chemical formula can be written as Ti3AC2, where A = Al, Si, Ge. This group comprises of (Ti3SiC2, Ti3GeC2 and Ti3AlC2). MAX phase properties are of more than two elements. They can be "sliced or diced" using a man- ual hacksaw. These materials are used in applications such as industrial robots, disc drives, electronics and MEMS devices.